2014
DOI: 10.1007/s00412-014-0479-4
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting behavior of heterochromatic and euchromatic chromosome portions and pericentric genome separation in pre-bouquet spermatocytes of hybrid mice

Abstract: The spatial distribution of parental genomes has attracted much interest because intranuclear chromosome distribution can modulate the transcriptome of cells and influence the efficacy of meiotic homologue pairing. Pairing of parental chromosomes is imperative to sexual reproduction as it translates into homologue segregation and genome haploidization to counteract the genome doubling at fertilization. Differential FISH tagging of parental pericentromeric genome portions and specific painting of euchromatic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…In spite of the known role of subtelomeric (bouquet) association in chromosome pairing ( Ishiguro et al, 2014 ; Scherthan et al, 2014 ), the location of the consubspecific sequence at the telomeric end was not essential for synapsis (p=0.9573, F-test). The PWD/PWD intervals of sufficient size rescued synapsis whether located at the centromeric (proximal, n = 14 cases), interstitial (n = 3), or telomeric (distal, n = 14) position ( Figure 3—source data 1 – 6 ).…”
Section: Resultsmentioning
confidence: 91%
“…In spite of the known role of subtelomeric (bouquet) association in chromosome pairing ( Ishiguro et al, 2014 ; Scherthan et al, 2014 ), the location of the consubspecific sequence at the telomeric end was not essential for synapsis (p=0.9573, F-test). The PWD/PWD intervals of sufficient size rescued synapsis whether located at the centromeric (proximal, n = 14 cases), interstitial (n = 3), or telomeric (distal, n = 14) position ( Figure 3—source data 1 – 6 ).…”
Section: Resultsmentioning
confidence: 91%
“…3b). Studies utilizing microscopy demonstrated that, during meiotic prophase, both chromosome ends attach to the nuclear membrane 25 and, in particular, the acrocentric ends tend to associate because of the frequent association of pericentromeric heterochromatin 26 . Our Hi-C results are consistent with these microscopic observations.…”
Section: Resultsmentioning
confidence: 99%
“…Meiotic homology search in many organisms is associated with chromosome movements in the presence of physiological DSBs 12 13 14 15 . In the asynaptic meiosis of the fission yeast Schizosaccharomyces pombe a synaptonemal complex is absent but chromosomes are aligned by oscillating nuclear mobility driven by the astral microtubule-bound spindle pole body (SPB) to which telomeres are attached, giving rise to the so-called horsetail nucleus throughout much of prophase I 7 16 .…”
mentioning
confidence: 99%